Volatile‐Rich Hydrothermal Plumes Over the Southern Central Indian Ridge, 24°49'S: Evidence for a New Hydrothermal Field Hosted by Ultramafic Rocks. (6th October 2022) - Surya Prakash, L.; John Kurian, P.; Resing, J. A.; Tsunogai, U.; Srinivas Rao, A.; Sen, K.; Lupton, J. E.; Baumberger, T.; Prajith, A.; Roy, P.
Abstract: Water column physico‐chemical studies were conducted over the southern Central Indian Ridge between 24°44'S and 25°52'S to identify and chemically characterize seafloor hydrothermal activity. High turbidity values were observed between 2300 and 2700 m with two distinct layers, between water depths of 2320–2500 m and 2510–2650 m, at two closely spaced CTD stations at 24°48.62'S (CTD‐17‐P5) and 24°48.68'S (CTD‐17‐P8). Elevated concentrations of dissolved Mn (DMn: 19–112 nM), dissolved Fe (DFe: 33–88 nM), methane (CH4 : 32–246 nM), elevated δ 3 He values (28%–88%), and stable carbon isotope ratios of CH4 confirm the hydrothermal origin. In plume layer‐1, the maximum concentrations were observed at 2375m at P8 and in plume layer‐2, the maximum concentrations were observed at 2570 m at P5. The stable isotope ratios of methane (δ 13 C‐CH4 ) show that heavier isotopes are enriched (−13.2‰ to −14.7‰) in the plume waters and are similar to vent fluids on the global mid‐oceanic ridges. Further, morphological and mineralogical studies of plume particles, collected from the plume layer‐2 maxima, clearly show the presence of barite, pyrite, chalcopyrite, and indicate possible venting of high‐temperature fluids in the vicinity of P5. Enrichment in methane relative to the other tracers and the general geochemical characteristics of these two plume layers, CH4 /Mn (1.8–2.2); CH4 /Δ 3 He (85–97 × 10 6 ), Mn/Δ 3 He (44–46 × 10 6 ), Fe/Δ 3 He (52–54 × 10 6 ), indicate that these plumes are formed from fluids released at the seafloor that circulated through ultramafic/gabbroic rocks. The high concentrations of dissolved gases and metals combined with the presence of sulfide particles in the water column provide evidence for a new ultramafic/gabbroic‐hosted hydrothermal vent field, at 24°49'S on the southern Central Indian Ridge. Plain Language Summary: Evidence for the seafloor hydrothermal activity was first discovered in 1970. Since then, numerous vent fields were discovered in Atlantic, Indian and Pacific Oceans. Among these three oceans, Indian Ocean is relatively less explored and most of the hydrothermal fields were discovered along the Central Indian Ridge. A multi‐disciplinary team, expertise in geophysics, geology, physical, chemical and biological oceanographers, has to work together to discover these fields. Extensive water column studies have been carried out on the southern Central Indian Ridge to identify plumes. High concentrations of manganese, iron, methane, and helium values between 2300 and 2700 m confirm the presence of hydrothermal plumes. The nature of the particles collected from these plumes shows that most of them are sulfides, sulfate and oxides of iron. The geochemical ratios in these plumes (combination of gas/metal and metal/gas) show that the fluid composition is controlled by ultramafic rocks. The chemical composition of both fluid and plume is mainly controlled by the rock type (basalt and/or ultramafic) of the sub‐seafloor. The high concentrations of gases and metals in the water column provide evidence for a new hydrothermal vent field, at 24°49'S on the southern Central Indian Ridge. Key Points: Chemical signatures in the deep waters of the southern Central Indian Ridge, at 24°49'S, provide evidence for hydrothermal plumes Enrichment of volatiles (helium and methane) over metals (manganese and iron) in plumes indicate the influence of ultramafic rocks Presence of sulfide and sulfate particles (pyrite, chalcopyrite and barite) in plumes may indicate the high‐temperature venting in the vicinity